Immunoglobulin G4-related disease, constitutional symptoms, human leukocyte antigen b27 positivity, and sacroiliitis - Shallu Verma; Lubna Khurshid; Prasad Rao Voleti; Anand Narayan Malaviya (Indian Journal of Rheumatology)
IgG4-related disease (IgG4-RD) is a relatively new clinical entity with protean manifestations that pose diagnostic difficulties especially so if the clinical features are atypical. Here we present a 55-year-old man with back-buttock pains, a knee and ankle arthritis with moderately severe constitutional symptoms. The acute phase reactants were high, and the test for HLA B27 was positive. Spondyloarthritis (SpA) was suspected but, because of the symptom-onset >45 years of age, infection and malignancy were also considered. Detailed investigations including a whole-body positron-emission tomography (PET) scan that showed hypermetabolic soft tissue thickening in the periaortic recess and at the base of the heart encasing root and ascending aorta. Fluorodeoxyglucose (FDG) uptake was also seen in the peripheral zones of the prostate, bilateral, parotid nodes, and in the right sacroiliac joint. A biopsy of the parotid gland nodule confirmed the diagnosis of IgG4-RD. The presence of features of inflammatory back-buttock pains, lower extremity oligoarthritis, good relief to non-steroidal anti-inflammatory drugs (NSAIDs), presence of HLA B27, and an acute involvement of the right sacroiliac joint were typical of spondyloarthritis. However, the moderately severe constitutional symptoms were not typical of SpA. Thus, this patient had both the IgG4-RD as well as SpA. Was the presence of HLA B27 incidental and the sacroiliitis was due to the infiltration of IgG4 cells or, he had true SpA with sacroiliitis and the IgG4 cell infiltration was incidental? This issue has been discussed in depth.